Modeling Relapsing Malaria: Emerging Technologies to Study Parasite-Host Interactions in the Liver - Voorberg-van der Wel, Annemarie; Kocken, Clemens H. M.; Zeeman, Anne-Marie (Frontiers in Cellular and Infection Microbiology, 2021)
Recent studies of liver stage malaria parasite-host interactions have provided exciting new insights on the cross-talk between parasite and its mammalian (predominantly rodent) host. We review the latest state of the art and and zoom in on new technologies that will provide the tools necessary to investigate host-parasite interactions of relapsing parasites. Interactions between hypnozoites and hepatocytes are particularly interesting because the parasite can remain in a quiescent state for prolonged periods of time and triggers for reactivation have not been irrefutably identified. If we learn more about the cross-talk between hypnozoite and host we may be able to identify factors that encourage waking up these dormant parasite reservoirs and help to achieve the total eradication of malaria.